Evidence for early fragmentation-reassembly of ordinary chondrite (H, L, and LL) parent bodies from REE-in-two-pyroxene thermometry. (1st December 2020) - Lucas, Michael P.; Dygert, Nick; Ren, Jialong; Hesse, Marc A.; Miller, Nathaniel R.; McSween, Harry Y.
Abstract: Ordinary chondrites (OCs) are variably thermally metamorphosed meteorites thought to originate from at least three different parent bodies (H, L, and LL) in the Main Belt of asteroids. The thermal evolutions of OC parent bodies are frequently explained by the onion shell model; however, a competing hypothesis is the fragmentation-reassembly model. The onion shell model proposes undisrupted, internally heated parent bodies with concentrically stratified thermal structure, and posits that OC petrologic types (i.e., 3–6) develop with increasing temperature and burial depth. In this model, petrologic types are inversely correlated with cooling rate in the parent body. The alternative fragmentation-reassembly model invokes catastrophic collisional disruption of parent bodies that initially possessed onion shell structures, followed by rapid reaccretion of hot fragments, forming rubble pile bodies. Fragmentation would result in fast cooling (quenching) of collisional fragments from the temperature experienced by the parent body at the time of collision. Discrimination between these two models may be possible via investigation of the thermal histories of OCs by application of geothermometry and geospeedometry, which are used to constrain the temperatures and rates through which igneous and metamorphic rock samples cool. Most published cooling rate data for OC parent bodies are based on methods that record rates through low closure temperatures (∼500–200 °C) rather than from peak metamorphic temperatures. Recently, a rare earth element (REE)-in-two-pyroxene thermometer has been shown to establish peak or magmatic temperatures (TREE ; Liang et al. [2013]) for rocks that cooled at moderate to fast geologic rates. We applied the REE-in-two-pyroxene method to determine peak temperatures for 18 OC samples (mostly type 6), in conjunction with conventional two-pyroxene thermometry (TBKN ; Brey and Köhler [1990]) and Ca-in-olivine thermometry (TCa-Ol ; Köhler and Brey [1990]), to determine closure temperatures and estimate cooling rates for OC parent bodies. Inconsistent with slow cooling rates expected within an onion shell structure, we obtain fast cooling at rates ≳0.3 °C/y from peak temperatures of ∼900 °C. Corroborating the TREE and TBKN measurements, TCa-Ol suggests that the OCs cooled through TCa-Ol closure temperatures (∼700 to 800 °C) at ∼10 −2 to 10 −1 °C/y. These cooling rates are three to six orders of magnitude faster than rates determined using methods sensitive to low temperature (≤500 °C) cooling (e.g., metallography, 40 Ar– 39 Ar ages, 244 Pu fission track). We developed a novel numerical thermal model that incorporates fragmentation of an initial onion shell body and reassembly into a rubble pile body that reproduces both the fast cooling from high temperatures and the slow cooling through low temperatures observed in chondritic meteorites. We hypothesize that OC parent bodies initially possessed onion shell thermal structures, but later experienced collisional breakup, then reaccreted rapidly to form thermally stable rubble-pile asteroids.